2018
DOI: 10.1177/0898264318767037
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Correlates of Financial Mistreatment in the National Elder Mistreatment Study Wave II

Abstract: Assessment of mental health is relevant and important in cases of financial abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 31 publications
3
30
0
Order By: Relevance
“…Findings from the present study align well with two recent studies (Acierno et al, 2018;Wood, Liu, Hanoch, & Estevez-Cores, 2016) that also found mental health to be an important correlate of self-reported FE among older adults. Wood et al (2016) found that numeracy (11-item scale), physical and mental health (as indicated by the 12-Item Short Form Health Survey, SF-12), younger age, and male sex were related to increased risk of FE.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Findings from the present study align well with two recent studies (Acierno et al, 2018;Wood, Liu, Hanoch, & Estevez-Cores, 2016) that also found mental health to be an important correlate of self-reported FE among older adults. Wood et al (2016) found that numeracy (11-item scale), physical and mental health (as indicated by the 12-Item Short Form Health Survey, SF-12), younger age, and male sex were related to increased risk of FE.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, findings suggest greater depressive symptoms in perceived FE older adults, a finding that is consistent with previous research on mental health correlates of FE (Acierno et al, 2018;Beach et al, 2010;FINRA Foundation, 2015;Ganzini et al, 1990;Lichtenberg et al, 2013) and elder abuse more generally (Dong & Simon, 2014;Roepke-Buehler et al, 2015;Santos et al, 2017). Due to the cross-sectional nature of the study, it is unclear whether depressive symptoms are a cause or an effect of perceived FE.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…There are multiple ways to enhance our understanding of the nexus between elder abuse and traumatic stress in order to advance research, theory, and practice. For example, the experience of elder abuse has only recently begun to be conceptualized as a traumatic stressor (Acierno et al, 2019;Jackson, in press;Ramsey-Klawsnik & Miller, 2017). Relative to other forms of trauma, such as child maltreatment (e.g., Hodgdon et al, 2018), little is known about the elder abuse characteristics that predict psychological, social, physical health, and other outcomes (Maschi, Baer, Morrissey, & Moreno, 2013).…”
mentioning
confidence: 99%